Acute kidney injury in critically ill surgical patients: Epidemiology, risk factors and outcomes. Issue 1 (16th December 2018) - Trongtrakul, Konlawij; Sawawiboon, Chaiwut; Wang, Amanda Y; Chitsomkasem, Anusang; Limphunudom, Ploynapas; Kurathong, Sathit; Prommool, Surazee; Trakarnvanich, Thananda; Srisawat, Nattachai
ABSTRACT: Aim: Acute kidney injury (AKI) is one of the most serious complications seen in intensive care units (ICUs). However, its epidemiology, risk factors and clinical outcomes in surgical critically ill patients remains unclear. Methods: A prospective cohort study was conducted in surgical intensive care unit (ICU) of the university hospital in Bangkok, Thailand. AKI was diagnosed according to the KDIGO 2012 criteria. Results: A total of 189 of the 400 patients enrolled in our study developed AKI (47.3%). The severity was: stage 1 = 29.6% of all AKI (56 cases), stage 2 = 30.7% (58 cases), and stage 3 = 39.7% (75 cases). Risk factors of AKI development included a higher BMI, a greater APACHE‐II score, septic shock, use of mechanical ventilation, acute medical complications during surgical admission, and pre‐existing chronic kidney disease. After adjustment for covariates, only the most severe stage of AKI (stage 3) was associated with increasing 28‐day ICU mortality compared with no AKI stage, HR = 7.75 (95% CI, 1.46–41.20, P = 0.02). Conclusion: Acute kidney injury is common and is associated with an increase in mortality in surgical ICU patients. There should be more focus on patients with AKI risk factors to prevent this deleterious event. Summary at a Glance: This study describes the clinical course and risk factors for adverse outcomes in a cohort of patients admitted to intensive care units with post‐surgical acute kidney injury.